ENHANCING ELEVENTH GRADE STUDENTS' WRITING ABILITIES IN DESCRIPTIVE TEXT BY USING RUNNING DICTATION (RD) TECHNIQUE - Frian Saputra; Vyna Yuniarti; Ari Kurniawati; Nurmala Dewi (Didascein : Journal of English Education, 2022)
The goal of this study is to see if there is a significant difference in writing abilities between students who are taught using running dictation and those who are not. The quasi-experimental method was used in this study, with a nonequivalent control group design. The population consisted of all eleventh-grade students at Vocational High School Rawas Ulu during the academic year 2021/2022. There were six classes totaling 280 students. The sample included 11.TKJ 1 as the experimental group and 11.TKJ 2 as the control group, selected using purposive sampling. The data was analyzed using the paired sample t-test and the independent sample t-test. Following the findings of this study, the average post-test was 69.31 for the control group and 74.38 for the experimental group. The independent sample t-test results show that the value of sig. (2-tailed) was 0.00 less than 0.05 at the level significant 0.05. While the obtained t-value was 11.809 higher than the critical t-table value of 1.664 with degree of freedom 78, As a result of the test calculation of the independent test t-test the t-obtain > t-table, the null hypothesis (Ho) is rejected, and the alternative hypothesis is accepted. It means that using the Running Dictation technique to teach writing achievement in descriptive text is effective.